Managing Postoperative Pain in Spinal Surgery - Nichols, Emma Hitt (MD Conference Express, 2015)
Management of pain following spinal surgery is important not only for patient outcomes but also for improving costs, complication rates, and patient experiences. In this session, presenters reviewed current guidelines and recommendations, the use of perioperative epidurals, ways to reduce tissue injury, and characteristics of current medications used postoperatively for spinal surgery.